Comparative eﬃcacy and residual toxicity of selective insecticides against Helopeltis theivora Waterhouse infesting Cocoa - Thube, Shivaji Hausrao; Pandian, R.T.P.; Bhavishya, A.; Nikoshe, Akash; Vanitha, P.; Mahapatro, G.K. (Journal of Plantation Crops, 2023)
Cocoa (Theobroma cacao L.) is an important beverage crop, commercially grown as a plantation crop. In the changed climate-scenario, tea mosquito bug species complex viz., Helopeltis theivora, H. bradyii and H. antonii are emerging as major threat to cocoa cultivation in India. Among these species, H. theivora is responsible for causing substantial crop-damage. The present investigation was carried out to evaluate the toxicity, eﬃcacy, and residual eﬀects of various test-insecticides (Bifenthrin, Clothianidin, Flonicamid, Imidacloprid, Quinolphos and Thiamethoxam) against H. theivora, a major pest of cocoa. The results revealed that bifenthrin exhibited the highest toxicity with an LC 50value of 0.36 ppm, while flonicamid displayed the least toxicity with an LC50 value of 130.20 ppm. Quinalphos exhibited higher toxicity than flonicamid, with an LC50 value of 100.48 ppm. Imidacloprid and thiamethoxam recorded higher toxicity, recording lower LC 50 values of 47.23 and 64.98 ppm, respectively. Clothianidin showed moderate toxicity with an LC50 value of 75.31 ppm against H. theivora. Field experiments assessed the eﬃcacy of the screened insecticides, revealing that bifenthrin and clothianidin were the most eﬀective in managing H. theivora infestations, resulting in the lowest pod infestation percentages of 10.11% and 13.84%, respectively. Conversely, flonicamid exhibited the least eﬀectiveness, with 37.82% pod infestation. Furthermore, this study investigated the residual toxicity of the insecticides in the field. Bifenthrin and clothianidin displayed persistent eﬀects, causing over 25% mortality of H. theivora even up to 30 days after application. Flonicamid, however, showed rapid loss of residual toxicity compared to other insecticides, with less than 25% residual toxicity reported after 10 days. Imidacloprid and thiamethoxam demonstrated more than 25% residual mortality on day 20 after application. In conclusion, this research underscores the varying toxicities and eﬃcacies of diﬀerent insecticides against H. theivora in cocoa plantations, with implications for eﬀective pest management strategies.